The Role of PSAK 73 and PSAK 71 in Enhancing Financial Reporting Transparency, Risk Management, and Reporting Quality: An Integrative Literature Review - Hicca Maria Gandi Putri Aruan; Debora Maureen; Engle Imelia Siagian; Cindi Clawidia Silitonga; Jonathan Pandjaitan (Golden Ratio of Data in Summary, 2026)
This study examines how the implementation of PSAK 73 on leases and PSAK 71 on financial instruments affects financial reporting transparency, risk management, and reporting quality. The study applies a descriptive qualitative design through an integrative literature review of accounting standards, peer-reviewed journal articles, and relevant academic literature. The findings show that PSAK 73 improves reporting transparency by requiring the recognition of right-of-use assets and lease liabilities, thereby reducing the potential for off-balance-sheet financing and providing a more complete representation of lease obligations. PSAK 71 improves the relevance and timeliness of credit risk information through the expected credit loss model, which requires entities to incorporate historical data, current conditions, and forward-looking economic information. However, both standards create substantial reporting complexity. PSAK 73 requires entities to determine lease terms, discount rates, contract modifications, and the present value of lease payments. PSAK 71 requires the estimation of probability of default, loss given default, exposure at default, and macroeconomic scenarios. Effective implementation therefore depends on reliable accounting information systems, high-quality data, strong internal controls, cross-functional coordination, and sound professional judgment. Practically, companies need to strengthen contract databases, credit risk models, employee competence, and governance procedures. This review contributes an integrated conceptual framework showing that the benefits of PSAK 73 and PSAK 71 for reporting quality depend not only on the standards themselves, but also on organizational readiness and implementation capability.